The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1515/astro-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular gas in high-mass filament WB673

Abstract: Abstract:We studied the distribution of dense gas in a filamentary molecular cloud containing several dense clumps. The center of the filament is given by the dense clump WB 673. The clumps are high-mass and intermediate-mass starforming regions. We observed CS (2-1), 13 CO (1-0), C 18 O (1-0), and methanol lines at 96 GHz toward WB 673 with the Onsala Space Observatory 20-m telescope. We found CS (2-1) emission in the inter-clump medium so the clumps are physically connected and the whole cloud is indeed a fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(89 reference statements)
2
7
0
1
Order By: Relevance
“…This quantitative analysis indicates the intense star formation activity in the thermally supercritical filament ns1. 2017) also reported a similar extended shell-like structure/bubble-shaped nebula in the same longitude direction (see Figure 5 in Kang et al 2012, and Figure 1 in Kirsanova et al 2017). In Figure 17b, the Galactic southern side of the extended structure is also presented using the Herschel 500 µm image, where our selected star-forming regions (i.e.…”
Section: Embedded Condensations In the Filament Ns1supporting
confidence: 62%
“…This quantitative analysis indicates the intense star formation activity in the thermally supercritical filament ns1. 2017) also reported a similar extended shell-like structure/bubble-shaped nebula in the same longitude direction (see Figure 5 in Kang et al 2012, and Figure 1 in Kirsanova et al 2017). In Figure 17b, the Galactic southern side of the extended structure is also presented using the Herschel 500 µm image, where our selected star-forming regions (i.e.…”
Section: Embedded Condensations In the Filament Ns1supporting
confidence: 62%
“…The configuration, commonly described as 'pearls on a string', was initially seen in infrared data from the Herschel space telescope (Arzoumanian et al 2011) and has since been recognised as a common feature of star formation. On the other hand, filaments of much larger scales have been found in other star forming regions such as NGC 6334 (Zernickel et al 2013), and gas bridges of a similar scale to those in S235 connect multiple developed HII regions in OMC-1 (Hacar et al 2017) and the large filament observed in molecular gas in WB673 (Kirsanova et al 2017). However the nature of the aforementioned filamentary systems differs markedly from those seen in S235, which instead connect clusters of YSOs rather than individual protostars, and have formed in the presence of-, and by interaction with-a single HII region.…”
Section: Ammonia Gas Bridges As Remnants Of Induced Fragmentationmentioning
confidence: 92%
“…Considering the locations of these sources, it is possible that they trace peculiar motions or flows associated with the Perseus spiral arm. Kirsanova et al (2017) found that high-mass star forming regions (HMSFRs) in the Perseus arm traced by 6.7 GHz methanol masers between 85 • < l < 124 • , and 173 • < l < 196 • are moving outward and rotate about the Galaxy at a higher velocity with respect to the gas tracers (CO and CS). As can be seen in Figure 7 of Kirsanova et al (2017), the kinematics of these HMSFRs are somewhat simiar to our group C SiO masers, which supports our viewpoint that there exist large scale peculiar motions in the Perseus arm.…”
Section: Moving Groups and High Speed Starsmentioning
confidence: 99%